Variabilidade espacial de atributos físicos de um neossolo flúvico submetido à diferentes tipos de uso e manejo do solo - Araújo, Daniel Roberto (2012)
The soil has, naturally, heterogeneity, ie, its attributes change in space and on time. In Semiarid this characteristic of the soil does not receive such important, often for lack of knowledge, working with the soil evenly. he characterization of the variability of soil attributes is necessary so that we can interpret the possible causes of variations in crop yields. The geoestatistic has been used often, specially in soil science as a way to analyze the behavior and distribution of soil propeeties in space. Thus, the objective of this study was analyze the spatial variability, through the tool GS+, the physical attributes of a typic fluvia underwent two systems use and management of soil: disking and mowing lines. The area managed by disking has 0.5 ha and the area has 2.5 ha mowing lines. Are located on the systematic plan of Experimental Farm in the Valley Curu Pemtecoste. Soil samples were taken in both disturbed and undisturbed areas obeying the spacing of 15 x 15 m totaling 99 points, 21 in the area with harrowing and 78 in the area by mowing between the rows. The mechanical resistance to penetration had the highest coefficient of variation. The density was the only attribute which there wasn’t spatial dependence structure. The other attributes (sand, clay, silt, micro and macroporosity and gravimetric soil moisture and the mechanical resistance to penetration) showed spatial dependence of medium until high. It was found through the maps generated by the software Surfer 8.0 sites of higher and lower concentrations in each area. It was observed that the mowing area is made between the lines showed lower values macroporosity and high penetration resistance, the constraint condition for the growth of roots.